2004
DOI: 10.1038/nature02204
|View full text |Cite
|
Sign up to set email alerts
|

The interface between silicon and a high-k oxide

Abstract: The ability to follow Moore's Law 1 has been the basis of the tremendous success of the semiconductor industry in the past decades. To date, the greatest challenge for device scaling is the required replacement of silicon dioxide-based gate oxides by high-k oxides in transistors. Around 2010 high-k oxides are required to have an atomically defined interface with silicon without any interfacial SiO 2 layer. The first clean interface between silicon and a high-K oxide has been demonstrated by McKee et al. 2 Nev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
198
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(205 citation statements)
references
References 25 publications
4
198
0
3
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Interest in SrTiO 3 stems from its applications as a substrate for high-T c superconductors, 20 in photocatalysis, 21 in ferroelectrics, 22 and as a buffer material for micro/nanoelectronic systems. [23][24][25] This is because SrTiO 3 boasts a number of attractive properties, including a highdielectric constant (high-κ) and suitable lattice parameter (0.3905 nm) for interfacing with other functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Interest in SrTiO 3 stems from its applications as a substrate for high-T c superconductors, 20 in photocatalysis, 21 in ferroelectrics, 22 and as a buffer material for micro/nanoelectronic systems. [23][24][25] This is because SrTiO 3 boasts a number of attractive properties, including a highdielectric constant (high-κ) and suitable lattice parameter (0.3905 nm) for interfacing with other functional materials.…”
Section: Introductionmentioning
confidence: 99%
“…In this way electronic defects such as broken bonds can be identified. The interface involving silicon (Si) and strontium titanate (SrTiO 3 ) [37] is the example that has been recently studied [2,16]. It was found that a specific coverage of one half monolayer of Sr atoms will chemically saturate the silicon substrate (leaving no dangling bonds), as the left panel of Figure 13.…”
Section: Computational Design Of Semiconductor Interfacesmentioning
confidence: 97%
“…Neither the chemically saturated interface nor the dependence of the insulating behavior on the stoichiometry at the interface could have been addressed using classical, interatomic potentials. Further discussions may be found in references [2,16,17]. …”
Section: Computational Design Of Semiconductor Interfacesmentioning
confidence: 99%
“…Each metal atom donates 2 electrons and, therefore, each dangling bond becomes occupied by an electron pair. As a result, this structure has no surface states in the band gap of the host [46], which is rather important for applications. The presence of a band gap adds to the resistance of the surface to oxidation [47] although one should note that both theory [48] and experiments [49] predict the silicide to become partly oxidized with formation of M-O-Si bonds.…”
mentioning
confidence: 99%